2016
DOI: 10.1016/j.micres.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vfr in the regulation of antifungal compound production by Pseudomonas fluorescens FD6

Abstract: Pseudomonas fluorescens FD6 has been shown to possess many beneficial traits involved in the biocontrol of fungal plant pathogens, such as Botrytis cinerea and Monilinia fructicola. Vfr (virulence factor regulator) a highly conserved global regulator of gram-negative bacteria, such as the human pathogen Pseudomonas aeruginosa, is required for the expression of many important virulence traits. The role of Vfr in the regulation of biocontrol traits, such as the production of antibiotics to control fungal pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In general, Vfr is not only related tightly to the pathogenicity of some bacteria, but also plays a critical role in their infection. In one other previous study, it was reported Vfr in P. fluorescens had a negative regulation on the biosynthesis of secondary antifungal metabolites, such as pyrrolnitrin, PLT, and DAPG ( Zhang et al, 2016 ). Knockout of the vfr gene brought increased production of antifungal compounds.…”
Section: Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Vfr is not only related tightly to the pathogenicity of some bacteria, but also plays a critical role in their infection. In one other previous study, it was reported Vfr in P. fluorescens had a negative regulation on the biosynthesis of secondary antifungal metabolites, such as pyrrolnitrin, PLT, and DAPG ( Zhang et al, 2016 ). Knockout of the vfr gene brought increased production of antifungal compounds.…”
Section: Disscussionmentioning
confidence: 99%
“…In P. chlororaphis PA23, ANR and PtrA were identified to mediate pyrrolnitrin production ( Nandi et al, 2016 ; Shah et al, 2016 ). In P. fluorescens FD6, RetS and Vfr were reported to regulate pyrrolnitrin biosynthesis ( Zhang et al, 2015 , 2016 ). In P. chlororaphis O6, RpoS and GacS deficiency could change the production of pyrrolnitrin ( Oh et al, 2013 ; Park et al, 2018 ).…”
mentioning
confidence: 99%
“…Examples of antifungal and secondary metabolites produced by Pseudomonas spp. include phenazines (Hu et al 2014), 2,4-diacetylphoroglucinol (Zhang et al 2016), pyoluteorin (Wu et al 2011), pyrrolnitrin (Zhang et al 2016), cyclic lipopeptides (Michelsen et al 2015), siderophores (Sulochana et al 2014), volatile compounds (Mannaa et al 2017), hydrolytic enzymes (Solanki et al 2014), and so on. Fluorescent pseudomonads, for example, Pseudomonas aeruginosa (Fatima and Anjum 2017), Pseudomonas putida (Yu and Lee 2015), and Pseudomonas fluorescens (Zhang et al 2016), are well-known to protect plants from fungal infections.…”
Section: Introductionmentioning
confidence: 99%
“…Although some regulators, such as the GacS/GacA system, the Quorum Sensing system, ANR, Vfr, and RpoS, were identified in certain Pseudomonas spp. to mediate pyrrolnitrin biosynthesis positively or negatively (Selin et al, 2010(Selin et al, , 2012(Selin et al, , 2014Haas and Keel, 2003;Nandi et al, 2016;Oh et al, 2013;Zhang et al, 2016), we still do not know much about the regulatory pathway of pyrrolnitrin biosynthesis in detail.…”
Section: Construction Of a Bmentioning
confidence: 99%